Character Mapping of University X Students: The Six Pillars of Character - Desy Vesya Simanjuntak; Arta Sriyuni Bakara; Epenta Sitepu; Ester Juliana Amorito Samosir; Katerina Barus; Neva Roulita Hutahaean; Setyo Rini Winarsih; Tria Febicha Oktavia Bangun; Rafael Lisinus Ginting (Cakrawala Sekolah: Journal of Multidisciplinary School Education, 2026)
Character education plays a crucial role in shaping students’ personalities as future leaders. However, in practice, a gap still exists between the understanding of character values and their implementation in everyday behavior. This study aims to describe the character profile of third-semester students at University X based on six character pillars—trustworthiness, respect, responsibility, fairness, caring, and citizenship—viewed from the aspects of knowledge, attitudes, and actions. A quantitative descriptive approach was employed, involving 70 students from seven faculties. Data were collected using a Situational Judgment Test (SJT) that measured the knowledge, attitude, and action dimensions of each character pillar and were analyzed manually by classifying scores into low, moderate, and high categories. The results indicate that students’ character across the six pillars is categorized as high in the knowledge and attitude aspects, but moderate in the action aspect. These findings suggest that although students have a strong understanding of character values, their application in real-life actions still needs to be strengthened through learning processes and role modeling within the university environment.